2013
DOI: 10.1042/bj20121580
|View full text |Cite
|
Sign up to set email alerts
|

Insight into S-adenosylmethionine biosynthesis from the crystal structures of the human methionine adenosyltransferase catalytic and regulatory subunits

Abstract: MAT (methionine adenosyltransferase) utilizes L-methionine and ATP to form SAM (S-adenosylmethionine), the principal methyl donor in biological methylation. Mammals encode a liver-specific isoenzyme, MAT1A, that is genetically linked with an inborn metabolic disorder of hypermethioninaemia, as well as a ubiquitously expressed isoenzyme, MAT2A, whose enzymatic activity is regulated by an associated subunit MAT2B. To understand the molecular mechanism of MAT functions and interactions, we have crystallized the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 42 publications
1
74
0
Order By: Relevance
“…A diverse series of structures are available for MAT enzymes from bacteria, rat, and human (4,(10)(11)(12), which, supported by a range of biochemical evidence, have provided significant insight into the enzymatic mechanism. SAMe synthesis follows an SN 2 catalytic mechanism (13,14) in which the reaction is initiated through a nucleophilic attack by the sulfur atom of methionine on the C5′ atom of ATP, which produces the intermediate tripolyphosphate (PPPi).…”
mentioning
confidence: 98%
“…A diverse series of structures are available for MAT enzymes from bacteria, rat, and human (4,(10)(11)(12), which, supported by a range of biochemical evidence, have provided significant insight into the enzymatic mechanism. SAMe synthesis follows an SN 2 catalytic mechanism (13,14) in which the reaction is initiated through a nucleophilic attack by the sulfur atom of methionine on the C5′ atom of ATP, which produces the intermediate tripolyphosphate (PPPi).…”
mentioning
confidence: 98%
“…Niflumic acid is a selective COX2 inhibitor and was selected as candidate for co-crystallization studies (see below). Another atypical member of the human SDR enzymes, MAT2B [19], yielded DSF hits like resveratrol (Table 1). MAT2B is an extended SDR member that functions as regulator of MAT2A (MATIIa), an enzyme important in S-adenosylmethionine synthesis.…”
Section: Differential Scanning Fluorimetry (Dsf) As Methods To Identifmentioning
confidence: 98%
“…Notably, the severe types of mutations, including nonsense, frameshift and splicing mutations, have been found exclusively in patients with the AR type (7,11,14,17,(21)(22)(23)(24). Because MAT I/III functions as a dimer, these types of mutations appear be p.Gly257Arg and p.Asp258Gly (7,(17)(18)(19)(20). It was suggested that a mutation in the other allele would exist; however, any mutation in other alleles was not identified by sequence analysis.…”
Section: Structural Analyses Of the Nine Mat1a Mutant Proteinsmentioning
confidence: 99%